(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Water is an irreplaceable natural resource and the cornerstone of aquatic and terrestrial ecosystems alike. Dams and reservoirs are critical infrastructure that support biodiversity, agriculture, potable water supply, hydropower generation, flood mitigation, and recreation. Despite their ecological importance, reservoir water quality remains vulnerable to seasonal fluctuations, anthropogenic pollution, and nutrient enrichment. The present study evaluates the physico-chemical characteristics and plankton community structure of Markandeya Dam, Kolar District, Karnataka, India, across pre-monsoon, monsoon, and post-monsoon seasons from February to July 2025. Phytoplankton (22 taxa) and zooplankton (14 taxa) were enumerated and subjected to nine diversity indices. A Water Quality Index (WQI) computed via the Weighted Arithmetic Index method yielded a value of 46.57, classifying the reservoir as moderately polluted. Nygaard's Water Quality Indices (NWQI) further indicated a mesotrophic trophic status. Most physico-chemical parameters conformed to WHO and BIS drinking-water standards; however, dissolved oxygen variability and elevated faecal coliform counts signal localized organic pollution and microbial contamination risks. Shannon–Wiener diversity indices for both phytoplankton (H' = 0–1.45) and zooplankton (H' = 0–0.92) indicated moderate pollution, with dominance by Chlorophyceae and Monogononta rotifers, respectively. Seasonal patterns revealed higher diversity and species richness during cooler pre-monsoon months and greater dominance during warm transitional periods. The integration of WQI, NWQI, and multi-index plankton assessment constitutes a robust and replicable framework for the ecological monitoring and sustainable management of tropical reservoir ecosystems.